2022
DOI: 10.1186/s12891-022-05902-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between magnetic resonance imaging and electrical impedance myography for evaluating lumbar skeletal muscle composition

Abstract: Background To compare electrical impedance myography (EIM) and MRI in assessing lumbar skeletal muscle composition. Methods One hundred forty-one patients (78 females, mean age 57 ± 19 years) were prospectively enrolled and underwent lumbar spine MRI, EIM with Skulpt®, and clinical evaluation including the questionnaire SARC-F. MRIs were reviewed to assess the Goutallier score of paravertebral muscles at L3 level and to calculate the cross sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Furthermore, several studies have established the relationship between EIM variables and structural features of muscles, as measured by MRI, CT, and DXA. Those studies also further supported the potential value of EIM in muscle structure assessment ( Anderson et al, 2014 ; McLester et al, 2018 ; van Rassel et al, 2019 ; Czeck et al, 2020 ; Hamel et al, 2020 ; Albano et al, 2022b , a ). While aforementioned correlation was validated, not all findings are fully consistent, since different techniques are sensitive to different pathological features of muscle ( Roy et al, 2019 ).…”
Section: Combination Of Eim and Morphological Assessmentsupporting
confidence: 59%
“…Furthermore, several studies have established the relationship between EIM variables and structural features of muscles, as measured by MRI, CT, and DXA. Those studies also further supported the potential value of EIM in muscle structure assessment ( Anderson et al, 2014 ; McLester et al, 2018 ; van Rassel et al, 2019 ; Czeck et al, 2020 ; Hamel et al, 2020 ; Albano et al, 2022b , a ). While aforementioned correlation was validated, not all findings are fully consistent, since different techniques are sensitive to different pathological features of muscle ( Roy et al, 2019 ).…”
Section: Combination Of Eim and Morphological Assessmentsupporting
confidence: 59%
“…Also, approaches such as machine learning, as previously described, 31 may be helpful for creating predictive models for determining muscle health based on EIM measurements across different frequencies. Though one commercially available EIM device providing a semiquantitative muscle health prediction was previously shown to have a weak correlation with PMA, 18 such machine learning models could be specifically trained for patients with PMA, potentially improving accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…17 Meanwhile, another study reported only a weak correlation between the semiquantitative grading of PMA on MRI and the fat percentage and muscle quality estimates by a commercial EIM device. 18 Thus, the relationship between the EIM readings at different frequencies with quantitative measurements of PMA on MRI scans, such as the functional cross-sectional area (fCSA) and fatty infiltration (FI), is unclear. Furthermore, whether surrounding tissue parameters such as dermal and subcutaneous layer thickness or echogenicity, which were previously shown to affect EIM readings confound the results in paraspinal EIM has not been previously reported.…”
Section: Electrical Impedance Myography (Eim) Is An Emerging Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The GSE98278 study was chosen for the analysis because it categorized AAAs as "large-sized" and "intermediate-sized" subgroups during patient enrollment [33]. After testing multiple SVM models with different When the correlation coefficient is less than 0.3, the probability of correlation is considered small [34]. With this cutoff value, correlation analysis for the hub genes showed that TAGLN, VCL, and GAJ1 were positioned as the center nodes (Fig 3E).…”
Section: The Efficacy Of Demgs To Identify Predetermined Aaa Subgroupsmentioning
confidence: 99%